Locating resistance to healthcare information technology: A Bourdieusian analysis of doctors' symbolic capital conservation. (12th July 2021) - Kumar, Mayank; Singh, Jang Bahadur; Chandwani, Rajesh; Gupta, Agam
Abstract: This research examines the socially significant issue of doctors' resistance to healthcare information technology (HIT) from the radical power perspective. It adopts Bourdieu's social practice theory to examine the interaction of HIT with the reproduction of doctors' historically rooted social standing through the doctor‐patient‐interaction (D‐P‐I) practice. Findings from our ethnographic enquiry at a large corporate healthcare organisation in India link doctors' historically rooted social standing to the symbolic recognition of their embodied emotional capital existing in tandem with their habitus. The symbolic recognition of emotional capital provided a better valorisation of clinical capital and allowed the accumulation of other forms of capital—institutionalised capital, social capital and economic capital—that formed doctors' capital structure and contributed to their social status. Doctors produced emotional capital by putting their habitus into practice and, in the process, reproduced its symbolic status and their social status linked to it. HIT challenged doctors to put their habitus into practice, thereby creating a perception of threat to emotional capital. Doctors' HIT resistance was a conservation strategy to reproduce their historically rooted higher social status. Findings from this study contribute to the literature on Power and IT resistance.